Hubungan Riwayat Terinfeksi SARS-CoV-2 dengan Persepsi Ibu Hamil Tentang Vaksinasi COVID-19 di Bekasi - Dora (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
COVID-19 vaccination has been proven effective in overcoming SARS-CoV-2 transmission globally. However, public perception of vaccination initiation still reflects significant variation among vulnerable populations such as pregnant women. This study aims to identify the relationship between a history of SARS-CoV-2 infection and pregnant women's perceptions of the COVID-19 vaccine in Bekasi. A cross-sectional design was applied in this study. The convenience sampling method was used to recruit prospective pregnant women as respondents with a total of 330 respondents. This study used the Perception Questionnaire about COVID-19 Vaccine as an instrument to assess respondents' perceptions. The Spearman Correlation test results showed a value of r=-0.332 with a p-value <0.0001, indicating that there was a significant relationship between a history of SARS-CoV-2 infection and pregnant women's perceptions regarding COVID-19 immunization. The value r=-0.332 indicated the strength of the relationship was moderate, with the direction of the relationship being inversely proportional, indicated by a minus (-) value for r. This means that the more pregnant women have been diagnosed positive for COVID-19, the more negative the mother's perception of giving the COVID-19 vaccine to pregnant women. Conversely, the less the mother's history of contracting COVID-19, the more positive their perception of the COVID-19 vaccine. The role of nurses is needed to educate proactively by starting discussions about vaccines with patients, peer group sharing, and making contracts for vaccination. A quasi-experimental research design is recommended for further research, specifically to test the effectiveness of the intervention program chosen to be implemented in the population of pregnant women.